2017
DOI: 10.1002/hep4.1113
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective on hepatitis B‐related single nucleotide polymorphisms and evolution during human migration

Abstract: Genome‐wide association studies have indicated that human leukocyte antigen (HLA)‐DP and HLA‐DQ play roles in persistent hepatitis B virus (HBV) infection in Asia. To understand the evolution of HBV‐related single nucleotide polymorphisms (SNPs) and to correlate these SNPs with chronic HBV infection among different populations, we conducted a global perspective study on hepatitis‐related SNPs. We selected 12 HBV‐related SNPs on the HLA locus and two HBV and three hepatitis C virus immune‐related SNPs for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Interestingly, the susceptible alleles in the HLA-DP/DQ locus are more frequent in Asian populations than in Caucasians, which might be one of the causes for higher prevalence of chronic HBV infections in Asia[ 22 , 113 ]. However, most of these susceptible alleles are not frequent in Africa, too, even though chronic hepatitis B is as prevalent in Africa as in Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the susceptible alleles in the HLA-DP/DQ locus are more frequent in Asian populations than in Caucasians, which might be one of the causes for higher prevalence of chronic HBV infections in Asia[ 22 , 113 ]. However, most of these susceptible alleles are not frequent in Africa, too, even though chronic hepatitis B is as prevalent in Africa as in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these susceptible alleles are not frequent in Africa, too, even though chronic hepatitis B is as prevalent in Africa as in Asia. Given that the predominant mode of transmission and HBV genotypes are different in Asia and Africa (vertical vs horizontal; B, C vs A, D, E; respectively), the genetic architecture for predisposition to chronic HBV infection also varies among these populations[ 7 , 113 ]. Hence, allele frequency distributions across human populations might give important insights into human-HBV co-evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In GWAS studies, HLA-DP and -DQ have been shown to consistently be associated with persistent HBV infection in East Asians [17][18][19][20][21][22][23] . However, such high-risk alleles are relatively rare in Africans [24] . Therefore, HBV infection elicited in the early stages of life remains an important mechanism of persistent HBV infection.…”
Section: Hbv Clearancementioning
confidence: 99%
“…Chronic persistent hepatitis B virus (HBV) infection is a global disease, and its prevalence is highest in Africa and East Asia [1][2][3][4] . The chronic relapsing inflammation caused by HBV leads to chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of HCC in the early, treatable stages leads to improved survival [7,8] . This is especially important for areas with endemic HBV infection [1][2][3]9] . The methods for early detection of HCC mainly rely on alpha-fetoprotein (AFP), AFP-lectin 3 fraction (AFP-L3), des-γ-carboxy prothrombin, and liver ultrasound (US) [5][6][7][8]10,11] .…”
Section: Introductionmentioning
confidence: 99%